Effect of Automated Writing Evaluation in Higher Education Academic Writing Performance - Mark Anthony Gavina; Leilani M. Ibay-Pamo (EDULANGUE, 2023)
This study aimed to identify the effects of Automated Writing Evaluation (AWE) in the academic writing of thirty-seven (n=37) higher education students as it is believed to address common errors encountered by higher education students in academic writing, specifically in grammar (S-V-A and verb tense). The study used a one-group pretest-posttest design that determined the specific effect of the formulated AWE treatment on the participants. The statistical evidence showed that the AWE tool (Grammarly) feedback provision, when paired with the teacher’s role as facilitator, significantly improved students’ academic writing in terms of S-V-A and verb tense. The findings also imply that the AWE, if integrated within the instruction using its feedback provision, can significantly improve students’ grammar usage and, consequently, their overall academic writing. These inarguable positive results of the AWE intervention used in this study create new assumptions to redefine not only the teachers’ feedback provision in students’ academic writing but also teaching writing in general.